PENGARUH EDUKASI TERSTRUKTUR TERHADAP PENGETAHUAN PASIEN DIABETES MELITUS TIPE 2 - Vina Putri Patandung; Mareyke Y. L Sepang; Ignatia Yohana Rembet (Jurnal Ilmiah Perawat Manado (Juiperdo), 2020)
Background hypoglycemia and hyperglycemia are complications that are frightening, dangerous, and potentially life threatening to patients with diabetes. Nurses can act proactively and change the way care is given. It is therefore necessary to develop safe and effective ways to proactively manage diabetes and hyperglycemia both in the hospital and at home. One of the nursing actions that is very important to do is providing structured health education to patients and families. The aim was to determine the effect of structured education with booklet media on the level of knowledge of T2DM patients being treated at Gunung Maria General Hospital. Method.This research method is a quantitative study with a quasi-experimental design.. The research design used pre-test and post-test for all respondents to determine the effect of structured education using booklet media on the level of knowledge of T2DM patients treated at Gunung Maria General Hospital. The sample used was 44 respondents. Results.The results showed that there was a significant increase in the level of knowledge before and after the intervention, with a p value <0.05.Conclusion. The conclusion is that structured education using booklet media has a significant effect on the level of patient knowledge about T2DM.